Turkish Validation of the PICCOLO (Parenting Interactions with Children: Checklist of Observations Linked to Outcomes). Issue 4 (24th June 2013) - Bayoğlu, Birgul; Unal, Özlem; Elibol, Fatma; Karabulut, Erdem; Innocenti, Mark S.
ABSTRACT Early positive parent–child interactions are important for child development. Intervention research focused on increasing positive parent–child interactions has demonstrated increases in desired parenting behaviors and improvements in child outcomes. Parent–child interaction research in Turkey has been limited because of the need for reliable and valid measures of parent–child interaction. The aim of this study was to explore the validity and reliability of a Turkish version of a psychometrically strong measure of parent–child interaction that was developed in the United States: the Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO). Mother–child interactions during a free‐play situation were scored using the Turkish translation of the PICCOLO. The Turkish PICCOLO demonstrated good reliability and validity; as good as that demonstrated in the original English‐language PICCOLO psychometric study. The Turkish PICCOLO meets the criteria established for a tool that will facilitate parent–child interaction research in Turkeyand appears to be practical and functional in evaluating the quality of parent–child interaction.